Analysis of porosity, sealer dissolution and apical extrusion of endodontic sealers: A micro computed tomography study - Neha Jasrasaria; Aseem P. Tikku; Ramesh Bharti (Elsevier, 2023)
Aim: The aim of the study was to determine the porosity, dissolution and apical extrusion of AH Plus, MTA Fillapex and EndoSequence BC sealer after immersion in phosphate buffered saline (PBS) using microcomputed tomography (micro-CT). Methodology: Forty-eight single-rooted teeth were selected. Gutta percha and one of the aforementioned root canal sealers was used for obturation using continuous wave technique. The specimens were scanned after obturation and after seven days of immersion in PBS, by using micro-computed tomography. Porosity, sealer dissolution and apical extrusion were calculated. Statistical analysis was done by using paired t-test, post hoc tukey test and Fischer exact test. Results: Significantly higher percentage of porosity and dissolution of sealer in the apical 4 mm was found for MTA Fillapex and EndoSequence BC sealer than for AH Plus. The incidence of apical extrusion was significantly more in MTA Fillapex (56.25%), followed by EndoSequence BC (31.25%) and AH Plus (0%). Conclusions: None of the three root canal sealers exhibited perfect three-dimensional obturation. The sealers manifested porosity, dissolution and apical extrusion to varying degrees both after obturation and after storage in PBS for 7 days.